Peningkatan Pemahaman Nilai Tempat dan Operasi Penjumlahan Bersusun Siswa Kelas I SD melalui Media Pintar Berhitung - Lailatul Rachmawaty; Nabila Mulyawati Hanafi; Kubbatut Diana; Agung Setyawan (Yayasan Citra Dharma Cindekia, 2026)
This study was motivated by the low mastery of place value concepts and long addition operations among first-grade students at SDN Socah 03. In addition, students tended to lose focus easily and showed limited participation during mathematics lessons. To overcome these problems, the researcher implemented “Smart Counting” media as a concrete, interactive, and engaging learning tool that suits the developmental characteristics of elementary school students. The study aimed to improve students’ understanding of units and tens, as well as their ability to perform long addition operations through the use of meaningful learning media. The research employed Classroom Action Research (CAR) consisting of two cycles, namely planning, action, observation, and reflection. The subjects of the study were 15 first-grade students in the even semester of the 2025/2026 academic year. Data were collected through classroom observations, interviews, and documentation. To ensure the validity of the data, source and technique triangulation were applied. The data were analyzed using a mixed descriptive approach, combining quantitative percentages to measure learning mastery and qualitative descriptions to capture classroom engagement. The results showed that the implementation of “Smart Counting” media improved both students’ learning outcomes and classroom engagement. Learning mastery increased from 80% in Cycle I to 93.3% in Cycle II. Students also became more focused, active, and enthusiastic during the learning process. Therefore, teachers are encouraged to use interactive and concrete learning media to create more effective and meaningful mathematics learning experiences in elementary schools.